TINGKAT PARASITASI PARASITOID TELUR PBPK PADA PERTANAMAN PADI DENGAN BEBERAPA KETINGGIAN TEMPAT BERBEDA - Resiani, Ni Made Delly; Sunanjaya, I Wayan (Informatika Pertanian, 2016)
Rice is the staple food of Indonesia's population. Various problems occur in an effort to increase production and productivity. One problem is the attack of yellow rice stem borer (PBPK) which may result in yield losses up to 90%. Utilization of parasitoid is an alternative to suppress the attack of Yellow Rice Stem Borer. The study was conducted in Tabanan, covering three locations with the altitudes of 50, 300, and 550 meters above sea leve, and at the Plant Pests and Diseases laboratory of the Faculty of Agriculture, University of Udayana. The study aimed to determine the effectiveness of parasitization of the best Yellow Rice Stem Borer as a natural control agent at different altitudes. The method used was survey by taking a sample group of Yellow Rice Stem Borer eggs with a purposive random sampling in the area of 2.5 hectares (one block in each location was an area of 0.5 hectares) at each location. Observations on parasitoid found in Yellow Rice Stem Borer eggs were done on parasitoid species diversity, equality, abundance, parasitation level, sex ratio, and the pattern of parasitoid invasion. The results showed three species of parasitoid eggs PBPK as biological control agents. Parasitation level of T. rowani and T. japonicum was the highest at the altitude of 50 meters above sea level, while T. schoenobii at the altitude of 300 and 500 meters above sea level.